Penguatan Kompetensi Agribisnis melalui Pelatihan Vokasional Berbasis Bahasa Inggris di Desa Kemiling - Nadella Lesmana; Ayu Dian Pratiwi Permatahati; Ainun Silvi Asya (Institut Agama Islam Ma’arif NU (IAIMNU) Metro Lampung, 2021)
Rural agribusiness workers in Kemiling Village face significant challenges in accessing global markets due to limited English proficiency, particularly in technical agricultural terminology and basic business communication. This community service program aimed to enhance vocational competencies through English-integrated training, addressing both linguistic barriers and agricultural skill gaps. Utilizing a participatory action research (PAR) approach combined with Hutchinson & Waters' (2017) ESP framework, the intervention implemented intensive workshops (10 sessions over 2 weeks) featuring: 1) contextualized agribusiness vocabulary acquisition, 2) simulated business negotiations, and 3) project-based evaluations. Results demonstrated measurable improvements: 72% of participants (n=25) mastered 50+ technical terms (pre-test: 20%), while 65% achieved functional transaction-level communication. The program also stimulated local innovation, evidenced by bilingual product labeling adoption in two UMKM. Findings validate that targeted vocational English training can effectively bridge rural-urban divides in global market participation, though sustained mentoring remains crucial for elder participants (35+ years) who showed slower adaptation. This model offers replicable strategies for human capital development in Indonesia's agricultural heartlands, particularly where language barriers constrain economic potential.